High speed stress measurement technique based on photoelastic modulator (PEM) and galvano-scanner. (January 2021) - Su, Fei; Zhang, Bowen; Li, Tenghui
Highlights: A full-field and high precision measurement mode of wafer residual stress was established. The measurement efficiency of residual stress was significantly improved by using galvanometer. The sources of measurement error and bottlenecks for the further improvement in scanning efficiency were analyzed. Abstract: In this work, a high-resolution method for residual stress measurement in silicon wafer based on photoelastic modulator was introduced. Then, to improve the measurement speed of this method due to its use of localized scanning mode, a fast scanning method using a galvanometer was proposed. This method maintains the high resolution of the photoelastic measurements but obtains improved measurement speed by keeping the sample stationary while the sample undergoes rapid laser scanning. The principle of the new scanning mode was introduced and its feasibility was verified, and it was found that the measurement speed was improved by a factor of three. Additionally, the sources of measurement error and bottlenecks for the further improvement in scanning speed were analyzed.